PEMBENTUKAN KARAKTER SISWA MELALUI PEMBELAJARAN MATEMATIKA - Suryani, Didik Rezki (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2016)
Educational success is not only measured by the value of a student’s academic mastery. The learning process is expected to bring students into the generation of educators in addition to the intelligence, and knowledge students also have the character values that are reflected in the behavior of daily life. At each level of education, learning math portion of lesson hours to get quite a lot compared to other subjects so that through the process of learning mathematics expected to form the character of students.            Math lesson plans should be designed optimally so that the purpose of forming the character of students through the learning of mathematics can be achieved. In this paper the authors provide examples of the application of learning mathematics curriculum in 2013. With a curriculum based learning stages in 2013 is expected to form the character of students, among others, respect for others, responsibility,and integrity.